2022
DOI: 10.3389/fmicb.2022.906312
|View full text |Cite
|
Sign up to set email alerts
|

Novel Quorum Quenching YtnP Lactonase From Bacillus paralicheniformis Reduces Pseudomonas aeruginosa Virulence and Increases Antibiotic Efficacy in vivo

Abstract: Bacterial infections have become increasingly difficult to treat due to the occurrence of antibiotic-resistant strains. A promising strategy to increase the efficacy of therapy is to combine antibacterials with agents that decrease pathogen virulence via the modulation of the quorum sensing (QS). Lactonases inhibit acylated homoserine lactone (AHL)-mediated QS in Gram-negative bacteria, including the leading nosocomial pathogen Pseudomonas aeruginosa. Here we describe the characteristics of heterologously expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…On the other hand, recent studies carried out by Djokic et al. ( 2022 ) showed that this enzyme in B. paralicheniformis ZP1 is highly effective in reducing the virulence of P. aeruginosa PAO‐1 in zebrafish. To our knowledge, this is the first time that this enzyme has been described in the species B. toyonensis .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, recent studies carried out by Djokic et al. ( 2022 ) showed that this enzyme in B. paralicheniformis ZP1 is highly effective in reducing the virulence of P. aeruginosa PAO‐1 in zebrafish. To our knowledge, this is the first time that this enzyme has been described in the species B. toyonensis .…”
Section: Discussionmentioning
confidence: 97%
“…Recently Peng et al (2021) have revealed that the YtnP protein of B. licheniformis strain T-1 causes a reduction in virulence of Aeromonas hydrophila ATCC 7966 in Carassius auratus both in vitro and in vivo. On the other hand, recent studies carried out by Djokic et al (2022) showed that this enzyme in B. paralicheniformis ZP1 is highly effective in reducing the virulence of P. aeruginosa PAO-1 in zebrafish. To our knowledge, this is the first time that this enzyme has been described in the species B. toyonensis.…”
Section: Discussionmentioning
confidence: 97%
“…Such combinations can be based not only on AMPs or antibiotics [ 43 , 44 ], but also on enzymes that are active against different G(+) and G(−) bacteria [ 45 , 46 , 47 ]. In vitro studies of the combined use of various AMPs derived from human and bovine lactoferrin with traditional antibiotics revealed the presence of a synergistic effect between polypeptides and antibiotics; however, the obtained results were insufficient to produce therapeutic effects in vivo [ 48 ]. In this regard, the search for new solutions among possible combinations of AMPs from lactoferrin continues.…”
Section: Discussionmentioning
confidence: 99%
“…QS was blocked through the degradation of QS signal molecules (AHL) by various species of B. paralicheniformis . Lactonase and acylase were found to degrade the lactone and acyl rings in the QS signal AHL, respectively [ 33 ]. Lb.…”
Section: Mechanism Of Qs Inhibitionmentioning
confidence: 99%